P133 Clinical and ultrasonographic enthesitis in inflammatory bowel disease patients with and without psoriasis. (27th May 2021) - Soriano, A; Bertolini, E; Bertani, A; Beltrami, M; Macchioni, P
Abstract: Background: Previous studies have reported the association between psoriasis (PsO) and inflammatory bowel disease (IBD). Coexistence of IBD and PsO has been associated with significant higher prevalence of enthesitis and dactylitis. The aim of the study was to compare the prevalence of clinical and ultrasonographic peripheral enthesis abnormalities in a consecutive series of patients with IBD and psoriasis (PsO) as compared to a group of IBD patients without psoriasis (IBD). Methods: 174 IBD consecutive patients [36 PsO and 138 IBD, M/F 91/83, mean age 42.6±14.7 years, mean disease duration 110 ±12.3 months] were recruited. A complete clinical examination, MASES and LEI scores, BASDAI, and dactylitis count, was performed at study entry. Laboratory markers (namely ESR, CPR, Hb, fecal calprotectin) were collected. Axial or peripheral spondyloarthritis (SpA) diagnosis was made using ASAS criteria. US examination was performed by a rheumatologist blind to clinical data. Lateral epicondyle of the humerus, distal quadriceps femoris insertion into the patella, inferior pole of the patella, tibial distal insertion of the patellar tendon, calcaneal insertion of the Achilles tendon, and plantar aponeurosis insertion were examined bilaterally. Knee and ankle joints were evaluated for synovial hypertrophy, PD signal and fluid effusion. Enthesitis was defined according to OMERACT and scored as 0–36 for GUESS and 0–136 for MASEI. Results: 146 patients (83.4%) showed structural damage at > 1 enthesis, 44 patients (25%) had at least 1 active enthesitis, with no significant difference between the two groups. PsO group showcased a significantly increased prevalence of patients having > 1 thickened enthesis (86.1% vs 63.9%, p=0.009) and of PD signal at knee examination (11.1% vs 2.2%, p= 0.034). Enthesis thickness was significantly increased in PsO, in every examined site. Enthesophyte length was significantly increased in PsO group at quadriceps tendon, patellar distal insertion and Achilles tendon. Conclusion: Presence of PsO and/or familiar history of PsO in IBD patients might represent a predisposing factor for the development of subclinical enthesytis as an extra-intestinal manifestation of IBD, during the disease course.